The Holy Qur'an Approach to Family Building - Muhammad, Salah Al- Din Awad (Journal of Islamic Sciences, 2022)
This study aimed at devise the rules, origins and foundations established by the Holy Qur'an to build a stable family, to identify the laws, conditions, and controls devised by scholars of interpretation, jurisprudence, and hadith in this area, and to select the most likely to achieve the total religion's objectives in its quest to form a stable family, while demonstrating the harmful customs and traditions that have worn the garb of religion. On the one hand, the study integrates the science of interpretation and jurisprudence. On the other hand, human sociology, which establishes the Qur'an's vision in establishing the family in accordance with the application of the rules of the inductive approach to explain the Holy Qur'an's texts and the Sunnah on family issues, and uses the comparative method of interpretation between the Holy Qur'an's texts and the Sunnah, as well as the sayings of scholars, to come up with a comprehensive vision that illustrates the Qur'an's. The study found that one of the most important rules and origins of the Qur'anic approach in the construction of the family is the nodal and material link, and that this Qur'anic approach has shown in explicit texts a number of provisions and meanings relating to the morals of cohabitation, which, among other things, lose the family's stability and tranquilly, as well as fail in its educational role. The norms and principles of terminating marital life in such a way that the impacts of this collapse are less destructive to family members and society were revealed via an investigation of various Qur'an texts found in family conflict instances. The findings revealed that the family's views, judgments, customs, and traditions are influenced by the culture of both ancient and modern cultures, with the Qur'an's origins, norms, and foundations proving to be the most effective in establishing a family.
Keywords: The Holy Qur'an; Curriculum; Origins; Rules; Ties; Family